Reflections on discussions about technical efficiency of innovativeness of countries - Wojciech Nasierowski (Foundations of Management, 2019)
The objective of this article is to outline various drawbacks of the studies on technical efficiency of pro-innovation activities at a national level. A better awareness of existing constraints may assist the readers and reviewers of the relative reports in a more critical assessment of the pre-sented results and help in planning the research. This article outlines several methodological prob-lems faced with conducting research on the technical efficiency of innovations. On the basis of the review of the subject-related literature, as well as press releases, numerous restraints prevailing in the currently used research approaches are presented. Some of these precincts are evidenced in the used methods: other may be rooted in the non-scientifically related intentions of the authors. Fre-quently, observations may drive the audience to the incorrect conclusions and opinions. The awareness of the consequences of these limitations may serve as a warning about the reliabil-ity of the results, their applicability for crafting policies, and country-to-country comparisons. However, various limitations originate from the very nature of the theme. Several propositions are specified about items to be kept in mind in order to minimize the negative impact caused by exist-ing drawbacks. These may serve as a guide to formulate research questions and hypotheses for verification in further studies. While each of the propositions stated independently may be labeled obvious, their simultaneous review many contribute to the streamlining further research and in the improvement of the quality of suggestions arrived at. The conclusions from the article may also pinpoint to these methodological issues that cause some of the publications on the subject to be of questionable value.
Keywords: B41; Q3; M20; 650; innovation; technical efficiency; methodology; research questions